Sztuczna inteligencja (AI), internet rzeczy (IoT) i sieć piątej generacji (5G) w nowoczesnych badaniach naukowych - Puślecki, Zdzisław W. (Człowiek i Społeczeństwo, 2021)
In the coming time, the innovative success of customer service will depend on having a data- driven strategy. Automation will play a key role in employee service initiatives. The progress and implementation of robot-based process automation, as well as machine learning, artificial intelligence (AI), the Internet of things (IoT), and the construction of the fifth generation 5G network will be important. Trends such as gamification, Big Data and AI are visible. Thanks to this, the right vision is created, supported by the necessary technical knowledge, to implement solutions that open the gate of undiscovered business potential. Modern technology is also becoming a tool of public surveillance. The aim of the study is to present artificial intelligence and the Internet of things as well as the construction of the fifth generation – 5G networks in the face of innovative challenges resulting from the economic crisis caused by the COVID-19 pandemic.